Analysis of Theodicy Concepts and Its Relevance during the COVID-19 Pandemic Period - Martin Elvis; Daniel Ronda (Jurnal Jaffray, 2021)
The COVID-19 pandemic problem raises many questions, whether the pandemic exists because of human sin? Is this suffering from God? Does God allow this to happen? If God is love, why should this pandemic occur? And various other kinds of questions. The purpose of this study is to find relevant values of theodicy concepts during the COVID-19 pandemic. This method uses qualitative research methods on the seven selected theodicy concepts and the latest research journals' results. Comprehensive results are obtained from the seven angles view of theodicy concepts relevant during the COVID-19 pandemic. From the study results, it can be concluded that the values of each theodicy concept studied gave appropriate contributions during the COVID-19 pandemic.